Es lebe die Landeshauptfrau – Österreichische Fachsprachen im DaF-Unterricht - Reinhold Utri (Linguistische Treffen in Wrocław)
Pluricentrism is already well-established in German studies – the concept is comprehensible, logical, and clear. It has been thoroughly developed, with several authors (e.g., Muhr) having described and explained the phenomenon of Austrian German in numerous essays, emphasizing that it is neither superior nor inferior, but should be regarded as equal. However, the necessary implications for dictionaries, translation studies (both the theoretical basis and practical application, e.g., at the European Union level), university practice (e.g., exercises in interpreting institutes, translation didactics), and general GFL (German as a Foreign Language) teaching in (Polish) schools and universities are still awaited. This article aims to provide examples of Austrian German to offer insight into how diverse the differences can be and to propose suggestions for addressing them. Even at an intermediate level (e.g., in Polish high schools), it is possible to teach learners grammatical, lexical, phonetic, idiomatic, and pragmatic units that they will later be able to use in communication with Austrian German speakers. Advanced learners (at the university level) should engage more intensively with literary and specialized texts of Austrian origin to better prepare for their professional work in language teaching or translation.